Nanostructure of PMMA/MAM Blends Prepared by Out-of-Equilibrium (Extrusion) and Near-Equilibrium (Casting) Self-Assembly and Their Nanocellular or Microcellular Structure Obtained from CO2 Foaming - Suset Barroso-Solares (MDPI AG, 2021)
Blends of poly(methyl methacrylate) (PMMA) and a triblock copolymer poly(methyl methacrylate)-b-poly(butyl acrylate)-b-poly(methyl methacrylate) (MAM) have been obtained following both out-of-equilibrium (extrusion) and near-equilibrium (solvent casting) production routes. The self-assembly capability and the achievable nanostructures of these blends are analyzed by transmission electron microscopy (TEM) regarding their production route and potential for the achievement of nanocellular foams by CO2 gas dissolution foaming. The influence of the initial nanostructure of the solids on the obtained cellular structure of bulk and film samples is determined by high-resolution scanning electron microscopy (HRSEM) for diverse foaming conditions (saturation pressure, saturation temperature, and post-foaming stage), taking into account the required use of a foaming mold to achieve foams from films. Moreover, the influence of the nanostructuration on the presence of solid outer layers, typical of the selected foaming process, is addressed. Finally, consideration of a qualitative model and the obtained results in terms of nanostructuration, cellular structure, and foaming behavior, allow proposing a detailed cell nucleation, growth, and stabilization scheme for these materials, providing the first direct evidence of the cell nucleation happening inside the poly(butyl acrylate) phase in the PMMA/MAM blends.